High variation in manufacturer-declared serving size of packaged discretionary foods in Australia. Issue 10 (17th March 2016) - Haskelberg, Hila; Neal, Bruce; Dunford, Elizabeth; Flood, Victoria; Rangan, Anna; Thomas, Beth; Cleanthous, Xenia; Trevena, Helen; Zheng, Jazzmin Miaobing; Louie, Jimmy Chun Yu; Gill, Timothy; Wu, Jason H. Y.
Abstract: Despite the potential of declared serving size to encourage appropriate portion size consumption, most countries including Australia have not developed clear reference guidelines for serving size. The present study evaluated variability in manufacturer-declared serving size of discretionary food and beverage products in Australia, and how declared serving size compared with the 2013 Australian Dietary Guideline (ADG) standard serve (600 kJ). Serving sizes were obtained from the Nutrition Information Panel for 4466 packaged, discretionary products in 2013 at four large supermarkets in Sydney, Australia, and categorised into fifteen categories in line with the 2013 ADG. For unique products that were sold in multiple package sizes, the percentage difference between the minimum and the maximum serving size across different package sizes was calculated. A high variation in serving size was found within the majority of food and beverage categories – for example, among 347 non-alcoholic beverages (e.g. soft drinks), the median for serving size was 250 (interquartile range (IQR) 250, 355) ml (range 100–750 ml). Declared serving size for unique products that are available in multiple package sizes also showed high variation, particularly for chocolate-based confectionery, with median percentage difference between minimum and maximum serving size of 183 (IQR 150) %. Categories with a high proportion of products that exceeded the 600 kJ ADG standard serve included cakes and muffins, pastries and desserts (≥74 % for each). High variability in declared serving size may confound interpretation and understanding of consumers interested in standardising and controlling their portion selection. Future research is needed to assess if and how standardising declared serving size might affect consumer behaviour.